NEEDS OF FAMILY MEMBERS IN THE WAITING ROOM OF AN INTENSIVE CARE UNIT - Gloriana Frizon; Eliane Regina Pereira Nascimento; Katia Cilene Godinho Bertoncello (Universidade Federal do Paraná, 2012)
This qualitative study aimed to investigate the needs of family members of patients hospitalized in an Intensive Care Unit. The study was undertaken in a large general hospital in the west region of Santa Catarina, involving 18 family members who granted interviews; Discourse of the Collective Subjective was used for processing the data. Two themes emerged from the accounts: Receiving information about the patient and Having more visiting hours. The results indicate that information given must convey confidence and security, and that the routine visits need to be reviewed. The study provides reflection about how Nursing acts with family members in critical care and considers that through welcoming actions the health professionals can contribute to how the family faces a member's hospitalization in an intensive care unit.